1999
DOI: 10.5014/ajot.53.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Protocol-Based and Adaptation-Based Occupational Therapy Interventions for Low-Income Elderly Persons on a Transitional Unit

Abstract: Findings support use of an individualized consultative intervention that addresses occupational performance areas and performance contexts combined with a protocol-based, hands-on intervention that addresses performance components and basic ADL for elderly persons with multiple chronic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…The conceptual rationale for the intervention was based on research demonstrating that older adults’ activity and lifestyle patterns are modifiable and predict aging outcomes [7, 12, 14, 15, 16, 17]. Consistent with this notion, health care professionals such as nurses and occupational therapists have recently placed increased emphasis on activity and lifestyle in attempting to enhance older adults health and well-being [18, 19, 20, 21]. …”
Section: Overview Of Study Methodologymentioning
confidence: 99%
“…The conceptual rationale for the intervention was based on research demonstrating that older adults’ activity and lifestyle patterns are modifiable and predict aging outcomes [7, 12, 14, 15, 16, 17]. Consistent with this notion, health care professionals such as nurses and occupational therapists have recently placed increased emphasis on activity and lifestyle in attempting to enhance older adults health and well-being [18, 19, 20, 21]. …”
Section: Overview Of Study Methodologymentioning
confidence: 99%
“…Among them, six publications report studies that document the effectiveness of OA-based interventions with clients following a cerebral vascular accident (CVA) (Dolecheck & Schkade, 1999;Gibson & Schkade, 1997;Johnson & Schkade, 2001), following a hip fracture (Buddenberg & Schkade, 1998;Jackson & Schkade, 2001), elderly clients with a variety of chronic illnesses (Spencer, Hersch, Eschenfelder, Fournet, & Murray-Gerzik, 1999), and adolescents with limb deficiencies (Pasek & Schkade, 1996). There are also a number of case examples that demonstrate the application of the OA model with different populations including children and adolescents with mental health problems (Bouteloup & Beltran, 2007), homeless persons (Johnson, 2006), persons with carpal tunnel syndrome (Martin, 2007), older workers (Moyers & Coleman, 1992), community-dwelling elders (Miller et al, 2002), forensic psychiatry (Stelter & Whisner, 2007), home health (Ford, 1995;Schultz & Schkade, 1994), and level II fieldwork students (Coates & Crist, 2004;Garrett & Schkade, 1995;Schkade, 1999).…”
Section: Occupational Adaptation (Oa)mentioning
confidence: 99%
“…Previous research by authors of the study reported here revealed that many elders adapted successfully to new living arrangements following hospitalization with surprising openness to new experiences and positive expectations (Hersch, Spencer, & Kapoor, 2003;Spencer, Hersch, Eschenfelder, Fournet, & Murray-Gerzik, 1999;Spencer, Hersch, Aldridge, Anderson, & Ulbrich, 2001). Indicators of successful adaptation were found to include maintenance or establishment of social relationships, engagement in valued activities, and getting personal care needs met.…”
mentioning
confidence: 61%